Mycotic Abdominal Aortic and Iliac Aneurysm Caused by Streptococcus equi Subspecies zooepidemicus Bacteremia - Madani, Anass; Zeebregts, Clark J.; Lamprou, Alexander; Tielliu, Ignace F. J. (AORTA, 2019)
This report describes a case of a taxidermist who presented with sepsis and excruciating back pain a few weeks after contact with a deceased horse. Streptococcus equi subspecies zooepidemicus (SESZ) was isolated from patient’s blood and two isolated mycotic aneurysms were found. The first was located in the distal abdominal aorta and the second in the right common iliac artery. Treatment consisted of penicillin administration for 6 weeks and surgical debridement of the infected tissue combined with autologous vein reconstruction. The patient was infection-free without complaints 1 year after discharge and the venous reconstruction was patent. Reports in literature of bacteremia with SESZ leading to the development of mycotic aneurysms are very scarce and show that prognosis is generally unfavorable.
Keywords: mycotic aneurysm; infectious aortitis; Streptococcus equi